EDUCATION FOR SUSTAINABLE DEVELOPMENT IN RUSSIA: CONCEPTUAL FOUNDATIONS, REALITIES AND PROSPECTS - A. N. Azizova (Ûg Rossii: Èkologiâ, Razvitie, 2015)
Aim. The present work reveals the foundations, realities and perspectives of education for sustainable development in Russia. In recent years, the Russian Federation passed a series of measures to introduce ideas of education for sustainable development in educational practice, including at a high political level. To date developed the "National strategy for education for sustainable development" and the "Plan of action on education for sustainable development" prepared by the working group under the leadership of the Member-correspondent of the Russian Academy of Sciences N.S. Kasimov. But unfortunately they have not yet been adopted at the State level. Location. Russian Federation Methods. Analytical review of current scientific, technical, normative and methodological literature that raises the issue of education for sustainable development. Results. The formation of a system of education for sustainable development involves a transition from traditional teaching to an environmentally oriented model, based on a broad interdisciplinary knowledge and on an integrated approach to the development of society, economy and environment. Main conclusions. Environmental education must be multi-level and continuous. It begins in the family and preschool, continues in middle school, followed by stages of University and postgraduate education. In connection with this, we believe, necessary to analyze in detail the situation in the field of education for sustainable development separately for pre-school, school, University and postgraduate levels of education.